2015
DOI: 10.1007/s10443-015-9452-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yarn Distortion on the Mechanical Properties of Fiber-Bar Composites Reinforced by Three-Dimensional Weaving

Abstract: A meso-structure model of fiber-bar composites reinforced by three-dimensional weaving (FBCR3DW) is proposed. Optical microscopy images of the preform structure revealed that the fibers along the circumference of the yarn cross-weave were twisted randomly due to alternating yarn winding on either side of the fiber bars during the manufacturing process. Sections of the cross-woven yarn were divided into five regions based on the twist characteristics. Stochastic function theory was used to describe the twist ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In practice, the distortion of yarn morphology caused by yarn squeeze is a real physical phenomenon and exhibits some certain random characteristics. Up to now, the influence of random yarn characteristics on the mechanical properties of fiber-reinforced composites has been a concern of some scholars [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Yushanov and Bogdanovich [ 22 , 23 ] developed an analytical method and analyzed the effects of random waviness of reinforcements on the elastic constants of unidirectional, biaxial and orthogonally woven composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the distortion of yarn morphology caused by yarn squeeze is a real physical phenomenon and exhibits some certain random characteristics. Up to now, the influence of random yarn characteristics on the mechanical properties of fiber-reinforced composites has been a concern of some scholars [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Yushanov and Bogdanovich [ 22 , 23 ] developed an analytical method and analyzed the effects of random waviness of reinforcements on the elastic constants of unidirectional, biaxial and orthogonally woven composites.…”
Section: Introductionmentioning
confidence: 99%
“…Amato et al [ 24 ] studied the nonlinear mechanical behavior of fabric composites caused by the change of yarn variation by a finite element method. Kang et al [ 25 ] investigated the effects of yarn torsion on the mechanical properties of 3D woven composites and pointed out that irregular yarn had a significant effect on the elastic properties and axial tensile strength of the yarn. Adumitroaie et al [ 26 ] found that the elastic constants of 2D orthogonal woven composites are related to yarn spacing and fluctuation and that the change of elastic constants will affect the failure load and initial failure position.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al 27 studied the compaction characteristics of multi-beam and multi-directional woven composite components by using the compaction system, revealed the relationship between volume fraction and compression stress, and obtained the law between compaction displacement, compaction load, component rebound, and forming process parameters. Kang 28 studied the influence of fiber rod diameter, array spacing and weaving tension force on the deformation of prefabricated parts, and established a mathematical model of guide bar deformation under the action of fiber tension, and controlled the deformation of guide array within a small range by controlling the value of tension force.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has the advantages of impact resistance, high damage tolerance, good interlayer performance, strong resistance to crack propagation, and good structural integrity. [5][6][7] It also provides the possibility and broad prospects for the transformation of composite materials from secondary load-bearing structure to main load-bearing structure.…”
Section: Introductionmentioning
confidence: 99%